Dieulafoy’s lesion versus peptic ulcer bleeding: clinical observation - Цуракова Е; Костовски О; Мишевски J; Исахи У; Тодоровска Б (My University, 2009)
INTRODUCTION: Upper gastrointestinal (UGI) bleeding is a common medical condition that results in high patient morbidity and medical care costs. The incidence of bleeding peptic ulcer (PU) has declined in recent decades making the uncommon causes of UGI bleeding relatively more common. Bleeding from Dieulafoy’s lesion (DL) is usually recurrent and can be difficult to detect in absence of active bleeding. AIMS AND METHODS: All patients diagnosed and treated with DL at the Clinic of Gastroenterohepatology and Clinic of Digestive surgery between January 1998 and April 2009 were studied. The group included 24 patients, 16 men and 8 women, mean age 64.2 yr. DL group was matched with a group of 48 PU bleeding patients by age, gender and comorbidities: hypertension, ischemic heart disease, cerebrovascular disease, diabetes, chronic renal failure/chronic hemodialysis treatment, prior peptic ulcer disease, and alcohol abuse. Hemodynamic parameters, endoscopic findings, modalities of endoscopic therapy, hemostasis rate, rebleeding rate, length of hospital stay and blood transfusion requirements were analyzed and compared between the two groups. RESULTS: In DL group, 8 patients presented with melena, 2 with hemathemesis, and 14 with both. Mean hemoglobin value at admission was 82.2 g/L. Most of the DLs (17) were located in the proximal stomach, 6 in the distal stomach, and 1 in the duodenum. Active bleeding was seen in 11 patients, while 13 presented with visible vessel. Endoscopic treatment was applied in 22 (91.7%) DL patients. Clipsing w/wo injection treatment was applied in 7 and injection treatment in 15 patients. Hemostasis was achieved in 15 (68.2%) patients, in 10 after repeated treatment. In one of the non-treated patients bleeding stopped spontaneously. Non-effective hemostasis/rebleeding occurred in 6 (27.3%) endoscopically treated patients and in one of the non-treated. All seven patients were treated surgically. Mean hospital stay of the patients with definitive hemostasis was 9.5 days and mean blood requirement was 3.3 units. The PU bleeding group consisted of 48 patients. Twenty-four of them presented with melena, 5 with hemathemesis, and 19 with both. Mean hemoglobin value was 89.7 g/L. One ulcer was located in the esophagus, 10 in the proximal stomach, 20 in the distal stomach and 17 in the duodenum. Active bleeding was registered in 14 patients, visible vessel in 13, and 21 patients had minor or no bleeding signs during endoscopy. Twenty (41.7%) patients received no endoscopic treatment. Among the 28 (58.3%) patients treated endoscopically, injection therapy was administered in 24, and clipsing w/wo injection therapy in 4 patients. Hemostasis was achieved in 24 of 28 (85.7%) endoscopically treated patients. Four patients rebled and 3 of them were treated surgically. Mean hospital stay of the patients with definitive hemostasis was 7.4 days and mean blood requirement was 2.4 units. CONCLUSION: Patients with DL more often require more than one endoscopy in order to achieve diagnosis and definitive hemostasis. There was no significant difference in any of the analyzed parameters between the two groups, except higher requirement for definitive surgery in the DL group.